Meaning above the head: combinatorial constraints on the visual vocabulary of comics. Issue 5 (3rd July 2016) - Cohn, Neil; Murthy, Beena; Foulsham, Tom
ABSTRACT: "Upfixes" are "visual morphemes" originating in comics where an element floats above a character's head (ex. lightbulbs or gears). We posited that, similar to constructional lexical schemas in language, upfixes use an abstract schema stored in memory, which constrains upfixes to locations above the head and requires them to "agree" with their accompanying facial expressions. We asked participants to rate and interpret both conventional and unconventional upfixes that either matched or mismatched their facial expression (Experiment 1) and/or were placed either above or beside the head (Experiment 2). Interpretations and ratings of conventionality and face–upfix matching (Experiment 1) along with overall comprehensibility (Experiment 2) suggested that both constraints operated on upfix understanding. Because these constraints modulated both conventional and unconventional upfixes, these findings support that an abstract schema stored in long-term memory allows for generalisations beyond memorised individual items.